2018
DOI: 10.1007/s11936-018-0674-3
|View full text |Cite
|
Sign up to set email alerts
|

The “Extreme Exercise Hypothesis”: Recent Findings and Cardiovascular Health Implications

Abstract: Purpose of reviewThe “Extreme Exercise Hypothesis” is characterized by a U-shaped or reverse J-shaped, dose-response curve between physical activity volumes and cardiovascular health outcomes. In this review, we summarize recent findings that may support or refute the “Extreme Exercise Hypothesis.” Furthermore, we discuss potential cardiovascular health implications of the cardiac anatomical, structural, contractility, and biomarker abnormalities that have been reported in some veteran endurance athletes.Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 54 publications
3
70
0
5
Order By: Relevance
“…Thus, it could be assumed that the volume of physical activity by combination of leisure time MVPA with heavy occupational lifting, results in overstrain, and cardiovascular damage, rather than optimized cardiovascular health. This notion is supported by previous ndings among both veteran athletes [32], and workers having both high OPA and high LTPA [33,34]. However, the lack bene cial effect from LTPA on BP was not re ected in the cross-sectional mean BP, showing higher levels of LTPA to relate to a lower BP, regardless of OPA level (Table 5).…”
Section: Study Ndingssupporting
confidence: 75%
“…Thus, it could be assumed that the volume of physical activity by combination of leisure time MVPA with heavy occupational lifting, results in overstrain, and cardiovascular damage, rather than optimized cardiovascular health. This notion is supported by previous ndings among both veteran athletes [32], and workers having both high OPA and high LTPA [33,34]. However, the lack bene cial effect from LTPA on BP was not re ected in the cross-sectional mean BP, showing higher levels of LTPA to relate to a lower BP, regardless of OPA level (Table 5).…”
Section: Study Ndingssupporting
confidence: 75%
“…Support for this theory has been evidenced in a registry of ~10.9 million runners, in whom marathons reportedly had 3 to 5 times higher incidence rates of cardiac arrest and death versus halfmarathons 88 . The proarrhythmic right ventricular (RV) remodeling and subsequent RV dysfunction that manifests after high volumes of long-term (months to years) excessive, sustained, high-intensity exercise training presumably explains the accelerated myocardial 91,92 , atrial fibrillation [93][94][95] , bradyarrhythmias 95 and diastolic dysfunction 96 reported in professional cross-country skiers and veteran runners 97 . Elevations in cardiac biomarkers of subclinical myocardial fibrosis including late gadolinium enhancement 92 , troponin and B-type natriuretic peptide appear to be strongly correlated with repetitive exposure to prolonged vigorous exercise 84,88,92,98 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T 16 needed to fully understand the clinical implications and pathophysiological profiles of plaque development that appear to be unique to long-term extreme endurance athletes 97,99 . Accordingly, additional evidence examining the cardiac benefits versus risk of extreme amounts of exercise is warranted.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Apart from general health benefits, it is well known that increasing PA has positive effects on pain in OA patients [1,10], suggesting a dose-response relationship. Currently, there is debate about the exact shape of the dose-response relationship between performed PA and health benefits [38][39][40]. Some research groups assume a (curvi)linear relationship implying the more PA the better [37,41,42], whereas other research groups assume an optimal range beyond which health benefits may be partially lost [38][39][40].…”
Section: Discussionmentioning
confidence: 99%